Chapter The Role of Mentors on the Development of Calling in Students: a 3-Year Investigation - Barbieri, Barbara (Studies on Adult Learning and Education, 2018)
In a three-wave longitudinal study, we investigated the role of mentoring on calling development. The results suggest that the mere presence of a mentor is associated with higher levels of calling and the development of a calling is fostered by the mentors' calling orientation, yet it is restrained by mentors' job and career orientation